Tuber yield, morphology, and chemical properties variability of sweet cassava germplasm - Tinuk Sri Wahyuni; Kartika Noerwijati (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
In Indonesia, the superior sweet cassava varieties are still limited due to the situation on which the majority of the superior varieties -bitter varieties- are used as industrial raw material until now. Therefore the availability of new high yielding of sweet cassava varieties is still needed. Assembling varieties requires the support of germplasm that has identified its superiority. The research objective was to evaluate tuber yield, morphology, and physico-chemical properties of cassava tuber from sweet cassava germplasm. A total of 75 accessions were characterized in Jambegede research station in February-November 2016, using Randomized Block Design. Variables observed included plant height, number of plants at harvest, harvest index, number and weight of tuber yield, and starch content. Physico-chemical analysis of tubers was carried out on 15 accessions with high tuber yields. Plant height at harvest was 393.2 cm in average. There were 10 accessions of sweet cassava with high fresh tuber yields ranging from 36.61 ton.ha-1 to 61.64 ton.ha-1, i.e MLG 10366, MLG 10365, MLG 10318, MLG 10197, MLG 10325, MLG 10341, MLG 10018, MLG 10279, MLG 10298, and MLG 10263. Physico-chemical analysis showed that the average of HCN content was 9.40 ppm, moisture content of 59.5 %, starch content of 28.8 % wb, and amylose content of 11.0 % wb. The bitter cassava with steamed tuber texture not cracked had relatively higher levels of HCN and water content, which was 82.88 ppm and 74.8 %, while the starch and amylose content was relatively lower (15.8 % wb and 5.5 % wb).